The Possibilities of Modern Ultrasound Scanning in Uveal Melanoma Extrascleral Growth Detection - A. G. Amiryan; S. V. Saakyan; G. P. Zakharova; A. Yu. Tsygankov (Oftalʹmologiâ)
Purpose. To determine the possibilities of modern ultrasound methods in the detection of uveal melanoma (UM) extrascleral growth (EG).Patients and methods. The work is based on the results of the examination and treatment of 170 patients with UM who underwent enucleation, including 106 (62.5 %) women and 64 (37.5 %) men aged 15 to 81 years (average — 52.9 ± 12.5). All patients underwent standard and special ophthalmological examinations, including grey scale echography and color Doppler Imaging on ultrasound system Voluson ® 730Pro device using a linear format probe with a central scanning frequency of 10–16 MHz. In all cases, a morphological study was carried out, and in 30 — a molecular genetic study.Results. UM EG was confirmed histologically in 33 patients — 19.4 % of 170 removed eyes. EG was recorded in all morphological types of UM, but more often in its more aggressive types-epithelioid cell and mixed cell types (χ2 = 6.236, p = 0.044). Significant correlations of EG presence with choroidal localization of UM (r = 0.150, p = 0.048), histological type (r = 0.151, p = 0.05) were revealed. In patients with EG, domed and irregular tumors were more often detected. The results of densitometric analysis of the tumor in patients with and without EG showed significantly higher acoustic density in patients with EG in the area of the base (A1) and central part (A2) of the tumor. In 16 (48.5 %) patients with EG, the growth was detected preoperatively — during ultrasound examination, in other cases-in 17 (51.5 %) patients, EG was established only intraoperatively or after pathohistological examination. The sensitivity of the high-resolution ultrasound technique for detecting EG was 48.5 %, specificity — 97.8 %, accuracy — 87.6 %, efficiency — 71.6 %, prognostic value of positive and negative results — 83.3 % and 97.8 %, respectively. The ROC analysis showed a clinical significance of 0.890 (95 % CI). A characteristic feature of patients with EG in the CDC mode was the visual determination of the total vascularization of the intraocular and extrascleral foci. Of the 30 patients who underwent molecular genetic testing, ERA was detected in 5 cases. All five patients had monosomy of chromosome 3.Conclusions. The paper presents the characteristic echographic (B-scan and color Doppler mapping) signs of extrascleral tumor growth, which allow us to adjust the tactics of surgical treatment. Data on the full or partial monosomy of chromosome 3 in the studied tumor samples in the presence of its extrascleral growth are presented.